2020
DOI: 10.1109/ted.2020.3025261
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Defect Characteristics and Carrier Transport Mechanisms in GaN Layers With Different Carbon Doping Concentration

Abstract: In this article, a metal/carbon-doped GaN (GaN:C)/Si-doped GaN (GaN:Si) structure was used to investigate the defect characteristics and carrier transport mechanisms in GaN:C layers with different carbon doping concentration. Capacitance-voltage, current-voltage, and deep-level transient spectroscopy measurements were performed at different temperatures. At forward bias, a pinning effect was found at the interface of the GaN:C/GaN:Si layer, due to the defects capturing electrons. The forward currents of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Electron traps with E1 and E2 were commonly observed in undoped, 18 intentionally n-type-doped, 19 and carbon-doped GaN layers, [9][10][11][12][13][14]20 which means that they are intrinsic defects not related to doping impurities. By changing the pulse duration t P , one can show that the amplitude of E1 increases linearly with ln(t P ) (Fig.…”
Section: A V P Bias At Off-statementioning
confidence: 99%
“…Electron traps with E1 and E2 were commonly observed in undoped, 18 intentionally n-type-doped, 19 and carbon-doped GaN layers, [9][10][11][12][13][14]20 which means that they are intrinsic defects not related to doping impurities. By changing the pulse duration t P , one can show that the amplitude of E1 increases linearly with ln(t P ) (Fig.…”
Section: A V P Bias At Off-statementioning
confidence: 99%
“…It was found that the high carbon-doped concentration (high carbon) 10 19 cm −3 has 171 V higher breakdown voltage than (low carbon) 10 18 cm −3 at 1 A cm −2 , Table 1. Carrier transport mechanisms [9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…Here, we consider that carbon would replace N or Ga, possibly acting as acceptor or donor [6][7][8]. At present, there are several leakage mechanisms on GaN-based epitaxial layers as shown in table 1 [9][10][11][12][13][14][15][16][17][18]. Among them, Zhou et al [9] have used accepted and donored ionization to analyze doped GaN high-electron-mobility transistors (HEMTS) leakage mechanism, and found space-charge-limited current (SCLC) models [9,10] make a key role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the commonly adopted method to reduce buffer leakage for power applications is to introduce carbon atoms in GaN, which may result in undesired trapping effects [4][5][6]. Many research groups have made a lot of effort to achieve a balance between breakdown voltage (BV) and trapping effects, such as optimizing the carbon concentration in GaN buffer [7][8][9], alternating carbon doping techniques [9], incorporating appropriate donor impurities to compensate carbon [10], removing local substrate [11], and so on. On the other hand, the structure of the buffer layer affects the trap density and the depletion of two-dimensional electron gas (2DEG).…”
Section: Introductionmentioning
confidence: 99%